MIRERC 075/2025: INFLUENCE OF WATER, SANITATION, AND HYGIENE PRACTICES ON DIARRHOEAL DISEASES IN CHILDREN UNDER FIVE YEARS OF AGE IN WESTLANDS SUB-COUNTY, NAIROBI COUNTY, KENYA - sunguti, Margaret (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
The health and well-being of under-five children are significantly influenced by water, sanitation, and hygiene (WASH) practices. According to the United Nations (2015), Sustainable Development Goals (SDGs) 6.1 and 6.2 aim to ensure universal access to safe drinking water and adequate sanitation by 2030. In its global Strategy for WASH (2016-2030), UNICEF recognizes the scale of the challenge facing the world if it is to succeed in achieving this vision and singles out urban WASH as one of the priority areas for increased engagement, to reach the most vulnerable, wherever they are. Diarrhoeal diseases, a leading cause of morbidity and mortality in this age group, are closely associated with inadequate WASH practices.The study aims to investigate the influence of Water, Sanitation, and Hygiene Practices on diarrhoeal diseases in children under five years of age. A cross-sectional descriptive study design will be employed utilizing a convergent mixed-methods approach. Quantitative data will be collected through structured questionnaires and observational checklists, while qualitative data will be gathered using key informant interviews and focus group discussions. The target population for this study will consist of caregivers of under five children residing in Westlands Sub-County, Nairobi County with a sample size of 375 households. The study will employ a cluster sampling technique. Quantitative data will be analyzed using statistical tools to identify patterns and relationships, whereas qualitative data will be subjected to thematic analysis to provide contextual insights. The study will contribute to the achievement of Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being) and SDG 6 (Clean Water and Sanitation). By improving WASH practices, it will also indirectly support SDG 1 (No Poverty) and SDG 4 (Quality Education) by minimizing economic strain and educational disruptions caused by preventable illnesses. Furthermore, the study will provide scientific value by filling existing knowledge gaps and laying the groundwork for future research in the field. Approval by the Institutional Research and Ethics Committee of Meru University, and informed consent from all study participants will be sought.